Propuesta de un plan estratégico para la planta procesadora de agua iglu de la ciudad de Nueva Loja, cantón Lago Agrio provincia de Sucumbíos, periodo 2016-2021 - Erraez Vicente, Mercedes Melania (2017)
The general objective of this thesis is to structure a Strategic Plan for the Water Processing Company "Iglú" located in the city of Nueva Loja, for the years 2016-2021, which allows the company to establish its long-term objectives, and determine the actions that must be carried out to reach them, having a clear idea of where the organization is located, where it wants to go and drawing the path that leads from one state to the other. Considered important conceptual issues for the development of the study, as a bibliographic basis, strategic planning and its importance, within the methods and techniques were used the deductive, research, analytical and statistical method, which served to meet the goals and planted objectives; In the theoretical-methodological framework, an interview was conducted with the manager, 9 employees and; surveys to 300 customers of the company water processing plant "Iglo. The interview made to the manager according to the objective was informative that allowed to obtain general information of the company, a structured interview was conducted to the employees to be able to know about the work environment of the company and finally a survey of the clients, a structure survey was presented with weighting of values according to the criterion that they consider most important with a higher and less important score with a lower score, in order to have a clearer picture of the company's situation. The information allowed a situational diagnosis of the company. An external analysis was carried out in the company, which allowed to define the opportunities and threats of the same, with which the EFE matrix was built, where the weighted total is 2.56. points, which indicates that the company is taking advantage of the opportunities to minimize the impact of the threats. The diagnosis of the company was made, and the strengths and weaknesses of the company were determined, with which the EFI matrix was elaborated, which gave the weighted rating of the company, which is 2.43, points; what represents that the company is weak internally, should be taken into account as it needs that the strengths are increased within the organization. Analyzing the internal and external environment allowed to build the SWOT matrix, establishing which are the main strengths, opportunities, weaknesses and threats, with which we build the high impact matrix, formulating the strategies FO DO FA DA, which allows to define the strategic objectives . With the definition of the strategic objectives, the proposal of Strategic Planning for the Igloo Company was made, which will serve as a tool for the company to attract new clients, increase their income and generate greater profitability. Finally, the main conclusions and recommendations were defined after finishing the research work.